Hermeneutics, irony and society: From the world of meaning to the world of consent - Mariscal Vega, Sara (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article presents a qualitative research on the concepts of hermeneutics and irony based on a review of Rorty’s text Contingency, Irony and Solidarity. Through a revision of the history of philosophical reason, it is shown how the hermeneutic engagement with the world is crossed by the ideas of solidarity and contingency. Finally, a reading of the hermeneutic circle is proposed as a vindication of a society concerned with justice that recognizes the lack of any metaphysical protection.